Estratégias de processamento textual: uma contribuição da Linguística Textual para a leitura dos gêneros textuais “charge” e “tira”, 2014 - Melo, Raquel Cristina de Souza (2014)
This research uses Textual Linguistics with the objective of proposing a reading which is based on socio-cognitive text processing strategies. Samples of two textual genres have been therefore chosen as a corpus: the "editorial cartoon" and the "comic strip". The hypothesis that the chosen genres may allow for the reader's construction when used according to the text processing strategies, providing them with the possibility of using their metageneric and reading competence, has been raised. A bibliographical research has been conducted on the work of Bronckart (2009), Marcuschi (2008, 2010, 2011), Kleiman (2011), Koch (2009, 2012), Koch & Elias (2012), Kato (1985), Lajolo (2006), Foucambert (1994) and Ramos (2009). Using the aforementioned theoretical foundation, a history of Textual Linguistics could be organised, which has allowed us to adopt the socio-cognitive interactionist definition for text, placing an emphasis on the interaction between reader and author. When it came to the corpus, three cartoons have been chosen which approach education, and three strips of encompassing different topics. Afterwards, the corpus was analysed using the reading strategies outlined in the theoretical foundation. The results of such practice demonstrate that the chosen textual genres ("cartoon" and "strip") have a sufficient number of elements for us to use the reading strategies, and may offer the reader the possibility of broadening their reading competence, as well as allowing them to develop a critical thinking through an entertaining kind of reading. Keywords: reading; textual linguistics; textual genres; cartoon; strip.